2009
DOI: 10.2174/1874279300903010013
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Providers'Providers' Role Legitimacy as Supporters of Their Patients' Alcohol Reduction

Abstract: Abstract:Although HIV care providers are strategically situated to support their patients' alcohol reduction efforts, many do not do so, sometimes failing to view this support as consistent with their roles. Using data collected from 112 HIV providers in 7 hospital-based HIV Care Centers in the NYC metropolitan area, this paper examines the correlates of providers' role legitimacy as patients' alcohol reduction supporters. Results indicate that providers (1) responsible for a very large number of patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Provider practices, attitudes, and training regarding provision of alcohol-related care may differ in these clinics from those in general primary care clinics. A previous study of 112 HIV care providers from 7 hospital-based care centers in New York City found that the majority of providers had not received any training regarding alcohol brief intervention and that many providers reported low levels of “role legitimacy” for supporting their patients in reducing their alcohol use (Strauss et al, 2009). In an audiotape study of 434 patients and 45 providers recruited from HIV clinics in four geographically-dispersed U.S. cities, the quality of patient-provider communication was worse for patients with unhealthy alcohol use than those without (Korthuis et al, 2011).…”
Section: 0 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Provider practices, attitudes, and training regarding provision of alcohol-related care may differ in these clinics from those in general primary care clinics. A previous study of 112 HIV care providers from 7 hospital-based care centers in New York City found that the majority of providers had not received any training regarding alcohol brief intervention and that many providers reported low levels of “role legitimacy” for supporting their patients in reducing their alcohol use (Strauss et al, 2009). In an audiotape study of 434 patients and 45 providers recruited from HIV clinics in four geographically-dispersed U.S. cities, the quality of patient-provider communication was worse for patients with unhealthy alcohol use than those without (Korthuis et al, 2011).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Since preventive brief interventions are most often provided in primary care, specialty HIV providers might need training in why and how to provide brief interventions (Strauss et al, 2009). Clinicians may be unaware of the effectiveness of brief interventions for reducing alcohol consumption, and the potentially greater impact of repeated brief interventions (Jonas et al, 2012), which could be integrated into HIV care given the frequency of visits.…”
Section: 0 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its substantial burden on HIV and related illnesses, alcohol use is often overlooked in HIV care (Chander et al., ; Conigliaro et al., ; Korthuis et al., , ; Metsch et al., ; Strauss et al., , ). Research suggests substantial barriers to HIV care providers' addressing alcohol use with their patients (Strauss et al., ,b). Both PLWH and HIV care providers perceive alcohol use as a low priority for HIV clinical care relative to other domains of care (Fredericksen et al., ).…”
Section: Addressing/reducing Alcohol Use Among Plwhmentioning
confidence: 99%